Sistem peradilan adat dalam kesatuan-kesatuan masyarakat hukum adat desa pakraman di Bali - I Ketut Sudantra; Tjok Istri Putra Astiti; I Gusti Ngurah Dharma Laksana (Pusat Kajian Bali Universitas Udayana, 2017)
This article aims to reveal the existence of customary court system on the customary law society entities of desa pakraman in Bali, both related to its institutional aspect, the kind of law its judgement was based, its authority or competency, and its work mechanism on reality. The study begins with revealing the normative aspect of customary court system according to applied regulation (awig-awig), which then empirically confirmed to affirm and explain the customary court system that lives on reality. Study’s result shows that customary court is an empiric fact that trully practiced on customary law society entities of desa pakraman in Bali. The institution that executing function in desa pakraman (Kertha Desa) is customary chiefs (prajuru) together with other village institution elements in desa pakraman (paduluan, kepala dusun/kepala desa). They execute court procession based on customary law and have authority to judge all case submitted to them, both in form of dispute or violation of regulation. Customary court settle every case submitted through a deliberation mechanism in a meeting named Paruman Prajuru